Profil Penulisan Skripsi Mahasiswa Pendidikan Bahasa Arab - Zalyana Zalyana; Meimunah SM (Kutubkhanah, 2012)
The aim of this research is to investigate the profile of students’ writing papers at the Arabic Education Department, Education and Teacher Training of State Islamic University Sultan Syarif Kasim Riau. The population of the research is all the wring papers of the Arabic Education Department which consist of 15 writing papers in the year of 2008/2009. Data collected by using documentation method and analyzed by content analysis. The research found that profile of the students’ writing paper is good that is covering aspect of the expressing of idea, regularity of idea, according to paragraph, election of mufradat, correctness in writing, equipment of amount of fi’liyah, according to amount of fi’liyah, according to marja’, usage of idhafi tarkib, usage of na’ty tarkib, usage of nakiroh isim, usage of ma’rifah isim, according to amount of ismiyah, according to and tazkir of ta’niz, usage of washal hamzah. While which still unfavorable cover the aspect of usage of Araby uslub, usage of Idiom, and usage of hamzah washal.